Escaping the Bonds of the Legacy: Step-Wise Migration to a Type-Safe Language in Safety-Critical Embedded Systems - Stilkerich, Michael; Schedel, Jens; Ulbrich, Peter; Schröder-Preikschat, Wolfgang; Lohmann, Daniel (Proceedings of the 14th IEEE International Symposium on Object/Component/Service-oriented Real-time Distributed Computing (ISORC '11), 2011)
Type-safe high-level languages such as Java have not yet found their way into the domain of deeply embedded systems, even though numerous attempts have been made to make these languages cost attractive. One major challenge that remains is the huge existing code base in many industries. Completely reengineering this code base is not viable for cost and time reasons. We present an approach that allows to isolatedly combine legacy software components and safe software components in an embedded system using the two most common communication idioms found in this domain. Our approach allows the developer to freely choose between hardware- and software-based isolation mechanisms. We demonstrate the feasibility of our approach by porting a non-trivial part of a real-world, hard real-time embedded avionics application. Our results show that the cost of this mixed-mode operation is on the same scale as the pure operation. © 2011 IEEE.
UnivIS-Import:2015-04-16:Pub.2011.tech.IMMD.IMMD4.escapi
Keywords: CiAO; Java; KESO; OSEK/VDX; embedded systems; memory protection; spatial isolation